Saving the modern soul : therapy, emotions, and the culture of self-help - Illouz, Eva, 1961- (University of California Press, 2008)
"The language of psychology is all-pervasive in American culture -- from 'The Sopranos' to 'Oprah', from the abundance of self-help books to the private consulting room, and from the support group to the magazine advice column. 'Saving the Modern Soul' examines the profound impact of therapeutic discourse on our lives and on our contemporary notions of identity. Eva Illouz plumbs today's particular cultural moment to understand how and why psychology has secured its place at the core of modern identity. She examines a wide range of sources to show how self-help culture has transformed contemporary emotional life and how therapy complicates individuals' lives even as it claims to dissect their emotional experiences and heal trauma"--Provided by publisher.